Socialisme ("Fabian essays in socialism"). Vert. [Uit het Engelsch] door F.M. Wibaut (Van Looy)
Internationale bibliotheek. 1. Grondslagen. [Door G.B. Shaw, S. Webb, W. Clarke en S.(H.) Olivier]. 1891. XXVIII, 210 p